Aggressive Histology and Extensive Metastasis Characteristic of Very Young Gastric Cancer (Less Than 30 Years): A Retrospective Clinical Audit - Krishnamoorthi, Narendran; Charles, Lourdhusamy; Nisha, Yadav; Dubashi, Biswajit; Ganesan, Prasanth; Kayal, Smita; Penumadu, Prasanth; Nelamangala Ramakrishnaiah, Vishnu Prasad; Ganesh, Rajesh Nachiappa (South Asian Journal of Cancer, 2023)
Objectives Gastric cancer (GC) is an aggressive disease and remains one of the most common causes of cancer-related mortality worldwide. Incidence of gastric cancer in young (GCY) varies between 2 and 8%. GCY faces unique challenges such as biological variation, diagnosis at an advanced stage, issues related to fertility preservation, and psychosocial considerations. This study aimed to find the differences in clinical characteristics and treatment outcomes of GCY compared to gastric cancer in older adults (GCO).Material and Methods This is a retrospective study from a tertiary care center. We screened records from 2015 to 2020, identified 33 records of GCY (less than 30 years), and compared the data with GCO (greater than 30 years) during 2015 and 2018.Results We identified 33 patients with GCY with a median age of 28 years (21–30) and a female to male ratio of 2:1. In GCY, 60% of patients presented with metastatic disease. Diffuse-type histology was more common in the GCY than in GCO (66.7% vs. 41.7%, p = 0.001). In patients with metastasis, multiple metastases were common in GCY compared to GCO (45% vs. 15%, p = 0.003). The median duration of follow-up for all patients was 27 (24–29) months. In GCY, the median OS was not reached for patients treated with curative intent, and it was 13 months for those treated with palliative intent.Conclusion The incidence of GCY in our study was like the western literature. Female patients with aggressive diffuse histology and multiple extensive metastases were characteristic of GCY. The survival outcomes were identical to GCO.
Keywords: young gastric cancer; aggressive histology; gastric adenocarcinoma